U.S. - INDIA Relations: Current Scenario - Shriparkash, (Integrated Journal for Research in Arts and Humanities, 2022)
Both their respective home attempts to achieve their respective domestic climate targets and the remotivated global efforts to boost climate ambition were shared by India and the United States. Both parties reiterated their promise to the crucial role of multilateral cooperation in addressing these global macroeconomic challenges as they discussed the current challenges to the global macroeconomic outlook in the context of the conflict in Ukraine, such as rising commodity and energy prices as well as supply constraints. They both reaffirmed their commitment to stepping up their efforts to put the G20 Common Framework for Debt Treatment into effect in a realistic, timely, organised, and coordinated way.